Health dialogue with non-native-speaking parents: Child health nurses' experiences. (December 2016) - Johansson, Lisbeth; Golsäter, Marie; Hedberg, Berith
The aim of this study was to explore child health care nurses' experiences of conducting health dialogues with non-native-speaking parents. In Sweden, it is not routine that all non-native-speaking parents are invited to a health dialogue. Regardless of language and cultural background, it is important that all parents have the same opportunities to participate. The data were obtained through two focus-group interviews and analysed using qualitative content analysis. The results revealed one theme Need for cultural awareness in the health dialogue and two categories: Overcoming feelings of uncertainty, with a need for more transcultural knowledge regarding what health and health promotion mean in other cultures; and Adapting the process of the health dialogue, whereby interpreters need knowledge about the intention of health dialogues and the content of the tool used in the encounter. Transcultural competence is needed in encounters with parents from other cultures.